CFs-Cu composite material and preparation method thereof
The preparation of CFs-Cu composite materials through gas-electric blending technology solves the problem of poor bonding force between carbon fiber and metal, significantly improves the mechanical strength and conductivity of the material, and achieves more efficient electron transmission.
Patent Information
- Application Number
- CN202510352142.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-25
AI Technical Summary
Among carbon fiber and metal composite materials, the chemical compatibility and bonding strength between carbon fiber and metal are poor, resulting in the failure to fully exert material performance.
PAN-Cu composite fibers are prepared by gas-electric blending technology, and CFs-Cu composite materials are formed through preoxidation and carbonization. The fibers and copper particles are physically wound and embedded with each other to form mechanical bonds.
The mechanical strength and toughness of the composite material are significantly improved, the overall performance of the material is improved, the hardness is increased by 5.2%, and the conductivity is increased by 28.3%.
Smart Images

Figure CN119876791A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite material preparation, and particularly relates to a CFs-Cu composite material and a preparation method thereof. Background Art
[0002] Copper (Cu) is the preferred material for wires and cables and other energy fields due to its excellent electrical and thermal conductivity and excellent processing performance. With the continuous advancement of science and technology, the performance requirements for copper materials are getting higher and higher. Graphene, as a promising material, can effectively balance the strength and conductivity of composite materials. However, graphene has the characteristics of high specific surface area. When added in high content in composite materials, it is easy to aggregate, which limits its performance. At the same time, carbon fiber (CFs) has become an indispensable component of composite materials due to its light weight, high strength, high modulus and good corrosion resistance. It has a wide range of applications in aerospace, automobiles, ships, sports equipment and medical equipment. Studies have shown that CFs-Cu composites composited with copper are not only lighter than traditional metal wires, but also have higher mechanical strength and greater load-bearing capacity. Therefore, combining the advantages of copper and carbon fiber, the development of CFs-Cu composites has important significance and broad application prospects.
[0003] However, there are many challenges in the development of carbon fiber and metal composites: the chemical compatibility and bonding between carbon fiber and metal are poor. The root of these problems is that carbon fiber has high inertness, low surface energy, lacks effective chemically active bonds, and has poor wetting properties between carbon fiber and metal. In order to improve this problem, researchers have tried a variety of surface pretreatment techniques to improve the interfacial bonding strength between carbon fiber and metal matrix. Guodong Zhang et al. used electroplating to electroplate carbon fiber onto the surface of copper sheet. Pei Wang et al. used chemical vapor deposition (CVD) to stack copper mesh and carbon fiber mesh layer by layer to prepare composite materials. Ziyou Wang et al. prepared composite materials by stacking carbon fiber and copper blocks through in-situ growth.
[0004] The present invention develops a novel method for preparing CFs-Cu composite materials, which provides excellent deposition efficiency for fibers through the technical means of gas-electrospinning and improves the jet stability of SBS; the preparation method can also increase the spinning rate, overcome the limitation of low electrospinning productivity, and prepare coaxial fibers more efficiently and safely.
[0005] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a CFs-Cu composite material and a preparation method thereof. The preparation method of the present invention enables the fibers to be efficiently attached to the copper particles, increases the degree of bonding between the fibers and the copper particles, and thereby enhances the performance of the composite material.
[0007] The technical solution adopted by the present invention to solve the above problems is as follows: A method for preparing a CFs-Cu composite material comprises the following steps: S1. Preparation of PAN-Cu composite fiber: dissolving polyacrylonitrile in N,N-dimethylformamide to obtain a PAN solution, adding spherical copper powder to the PAN solution, mixing evenly to obtain a PAN-Cu dispersion, and subjecting the PAN-Cu dispersion to gas-electro-spinning to obtain a PAN-Cu composite fiber; S2. Pre-oxidation of PAN-Cu composite fiber: After drying the PAN-Cu composite fiber, place it in a carbonization furnace and keep it at 120℃~150℃ for 30min, then heat it to 180℃~200℃ and keep it for 30min, and finally heat it to 220℃~240℃ and keep it for 1h; S3. Carbonization of PAN-Cu composite fibers: The pre-oxidized composite fibers were placed in a tubular furnace, heated to 800°C-950°C in an inert gas atmosphere, and kept warm for 2 hours to obtain a CFs-Cu composite material.
[0008] Preferably, the mass ratio of the polyacrylonitrile, N,N-dimethylformamide and spherical copper powder is 1:9:1-2.
[0009] Preferably, the gas-electrospinning method includes: injecting the PAN-Cu dispersion into a syringe, spinning with a coaxial needle, conveying the PAN-Cu dispersion with an inner shaft, ejecting a high-pressure airflow with an outer shaft, applying a voltage of 3 to 5 kV between the tip of the coaxial needle and a receiver, and depositing the PAN-Cu composite fiber on the receiver.
[0010] Preferably, the specification of the syringe is 25 mL.
[0011] Preferably, in the coaxial needle, the inner shaft is a 17-gauge needle with an inner diameter of 1.07 mm and an outer diameter of 1.70 mm; the outer shaft is a 13-gauge needle with an inner diameter of 1.90 mm and an outer diameter of 2.40 mm.
[0012] Preferably, the inner shaft delivers the PAN-Cu dispersion at a stable flow rate of 4 to 8 mL / h, and the outer shaft sprays a high-pressure airflow of 0.35 to 0.55 MPa and 25 to 40 LPM.
[0013] Preferably, the coaxial needle moves back and forth at a speed of 10 to 30 mm / min; the distance between the coaxial needle and the receiver is 25 to 40 cm; the receiver is a roller collector with a rotation speed of 10 to 30 rpm.
[0014] Preferably, the drying in step S2 is to place the obtained PAN-Cu composite fiber in a vacuum drying oven at 60° C. for 24 hours to remove excess solvent.
[0015] Preferably, the inert gas is argon.
[0016] Preferably, the heating rate is 5°C / min.
[0017] Preferably, when preparing the CFs-Cu composite material, the ambient temperature is 25°C to 30°C.
[0018] The present invention also provides a CFs-Cu composite material prepared by the above preparation method.
[0019] The present invention also provides a Cu / CFs-Cu composite powder, the raw materials for preparing the Cu / CFs-Cu composite powder include the above-mentioned CFs-Cu composite material, copper powder and ethylene glycol.
[0020] Preferably, the mass volume ratio of the copper powder to the ethylene glycol is 1 to 2:10; the mass volume ratio of the copper powder to the CFs-Cu composite material is 500 to 1000:1 Preferably, the preparation method of the Cu / CFs-Cu composite powder comprises the following steps: adding copper powder to ethylene glycol, stirring until the copper powder is evenly dispersed in the ethylene glycol; then adding the above-mentioned CFs-Cu composite material, stirring, and then filtering the Cu / CFs-Cu slurry onto a polytetrafluoroethylene filter membrane through a vacuum filter. Finally, the Cu / CFs-Cu slurry on the polytetrafluoroethylene filter membrane is placed in a vacuum drying oven for drying to obtain a Cu / CFs-Cu composite powder.
[0021] Preferably, the drying conditions are -0.8 MPa, 60°C, and 24 hours.
[0022] The present invention also provides a Cu / CFs-Cu bulk material, the raw materials for preparing the Cu / CFs-Cu composite powder include the above-mentioned Cu / CFs-Cu composite powder.
[0023] Preferably, the preparation method of the Cu / CFs-Cu bulk material comprises the following steps: placing the above-mentioned Cu / CFs-Cu composite powder in a tubular furnace, heating it to 800°C~950°C in an inert gas atmosphere, keeping it warm for 2 hours, and obtaining a reduced powder; using powder metallurgy to prepare a Cu-based composite material from the obtained powder; placing the Cu-based composite material in a tubular furnace, heating it to 800°C~950°C in an inert gas atmosphere, keeping it warm for 2 hours, and sintering.
[0024] Preferably, the powder metallurgy method specifically comprises: charging the obtained powder into a steel mold, and cold pressing the powder into a sample with a diameter of 25 mm at a pressure of 300 to 400 kN and holding the pressure for 300 to 600 seconds. The present invention has the following beneficial effects:
[0025] The present invention uses the technical means of gas-electric blending to form a mechanical bond between the fiber and the copper particles by physical entanglement and mutual embedding, so that the fiber is efficiently attached to the copper particles, the degree of bonding between the fiber and the copper particles is increased, and the performance of the composite material is enhanced. The preparation method of the present invention can form a stable interface layer on the interface between the fiber and the copper particles, which can effectively transfer stress and reduce stress concentration, significantly improve the mechanical strength and toughness of the composite material, and enhance the overall performance of the material.
[0026] The present invention successfully prepared PAN-Cu composite fiber by using gas-electric blending technology, and finally obtained CFs-Cu composite material after pre-oxidation and carbonization treatment. In the CFs-Cu composite material, carbon fiber and copper powder form a stable interface layer by physical entanglement and mutual embedding. This structure effectively promotes the transmission of stress and reduces stress concentration, thereby significantly improving the overall performance of the material. The bonding force problem between carbon fiber and copper powder is successfully solved.
[0027] Compared with pure copper, the hardness of the CFs-Cu composite material prepared by the present invention is increased by 5.2% and the conductivity is increased by 28.3%. This technical means not only enhances the mechanical strength of the composite material, but also improves the conductivity, making the electron transmission more efficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Characterization images of the CFs-Cu composite material prepared in Example 1: (a) SEM image of the original spherical copper powder; (b) infrared characterization image of CFs-Cu; (c) Raman characterization image of CFs-Cu; (d) SEM image of CFs-Cu; (e) EDS image of CFs-Cu.
[0029] Figure 2Characterization pictures of the Cu / CFs-Cu composite powder prepared in Example 2: (a) SEM picture after tableting; (b) performance comparison of Cu / CFs-Cu and Cu; (c) EDS picture of Cu / CFs-Cu. DETAILED DESCRIPTION
[0030] In order to make the technical problems, technical solutions and technical advantages to be solved by the present invention clearer, the following will be described in detail with reference to specific examples, but the protection scope of the present invention is not limited to the following specific embodiments, and the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, and are not limitations of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0031] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0032] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0033] The materials used in the following examples are as follows: Polyacrylonitrile (PAN, Mw = 150,000) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Spherical copper powder (25 μm in diameter) was purchased from Chunxu Metal Materials Factory, Nangong City, Xingtai City, Hebei Province; N ,N ,Dimethylformamide (DMF, reagent grade, 99.5%) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Ethylene glycol (EG, spectrally pure, ≥99% polyester grade) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0034] All reagents were used without further purification. Embodiment 1:
[0035] A method for preparing a CFs-Cu composite material comprises the following steps: S1. Preparation of PAN-Cu composite fiber: 2g polyacrylonitrile was dissolved in 18g N,N-dimethylformamide, and stirred at 250r / min for 2h to obtain a 10wt% PAN solution. 2g spherical copper powder was added to the 10wt% PAN solution and mixed evenly to obtain a PAN-Cu dispersion. The PAN-Cu dispersion was injected into a 25mL plastic syringe and spun with a coaxial needle. The inner shaft was a No. 17 needle (inner diameter 1.07mm, outer diameter 1.70mm), and the outer shaft was a No. 13 needle (inner diameter 1.90mm, outer diameter 2.40mm). The inner shaft transports PAN-Cu dispersion at a steady flow rate of 8 mL / h, and the outer shaft sprays a high-pressure airflow of 0.55 MPa and 25 LPM. The needle is placed on a reciprocating platform, and the moving speed is set to 30 mm / min. A roller collector is placed 40 cm away from the needle, and the speed is set to 30 rpm. A voltage of 5 kV is applied between the tip of the coaxial needle and the receiver to deposit the composite fiber on the silicone oil paper. The ambient temperature is between 25 and 30 ° C, thereby preparing PAN-Cu composite fibers. S2. Pre-oxidation of PAN-Cu composite fibers: After spinning, the membrane was removed and the obtained fiber membrane was placed in a vacuum drying oven at 60°C for 24 hours to remove excess solvent. The dried fiber was placed in a carbonization furnace and kept at 150°C for 30 minutes, then heated to 200°C for 30 minutes, and finally heated to 240°C for 1 hour to pre-oxidize the fiber membrane in the air. S3. Carbonization of PAN-Cu composite fibers: The pre-oxidized composite fibers were placed in a tubular furnace, heated to 800°C at a rate of 5°C / min in an argon atmosphere, and kept warm for 2 h to obtain a CFs-Cu composite material. Embodiment 2:
[0036] The preparation method of Cu / CFs-Cu composite powder comprises the following steps: adding 20g copper powder to 200mL ethylene glycol, stirring at a speed of 500r / min for 30min, so that the copper powder is evenly dispersed in the ethylene glycol; then adding 0.02g of the CFs-Cu composite material of the above-mentioned embodiment 1, stirring for 30min, and then filtering the Cu / CFs-Cu slurry onto a polytetrafluoroethylene filter membrane through a vacuum filter. Finally, the Cu / CFs-Cu slurry on the polytetrafluoroethylene filter membrane is placed in a vacuum drying oven, evacuated to -0.8MPa, and dried at 60°C for 24h to obtain a Cu / CFs-Cu composite powder. Embodiment 3:
[0037] The preparation method of the Cu / CFs-Cu bulk material comprises the following steps: placing the Cu / CFs-Cu composite powder of the above-mentioned embodiment 2 in a tubular furnace, heating it to 800°C at a rate of 5°C / min in an argon atmosphere, keeping it warm for 2 hours, reducing the Cu oxidized during the preparation process to obtain a reduced powder; using a powder metallurgy method to prepare a Cu-based composite material from the obtained powder, loading the mixed powder into a steel mold, and cold pressing it at a pressure of 400 kN for 300 seconds to form a Cu-based composite material with a diameter of 25 mm; placing the Cu-based composite material in a tubular furnace, heating it to 800°C in an inert gas atmosphere, keeping it warm for 2 hours, and sintering it.
[0038] Comparative Example 1: The pure copper sample was pressed and sintered, and the preparation conditions were the same as those of Example 1-3, except that no polyacrylonitrile was added during the preparation process.
[0039] The materials obtained in the examples and comparative examples were characterized. The characterization results of the CFs-Cu composite material obtained in Example 1 are as follows: Figure 1 The characterization results of the Cu / CFs-Cu composite powder prepared in Example 2 are shown in Figure 2 shown.
[0040] The microstructures of Cu and CFs-Cu are shown in Figure 2. Figure 1 (a), 1(d). 1(a) shows that the original spherical copper powder has a smooth surface and a round shape. Figure 1 (d) It can be seen that a large number of fibers are attached to the round copper particles. The fiber surface is smooth and has no obvious defects. Figure 1 (e) EDS shows that the copper element is surrounded by a large amount of carbon elements, proving that the fiber is successfully attached to the surface of the copper particles.
[0041] Figure 1 (b) is the infrared characterization of CFs-Cu, from bottom to top, they are untreated PAN-Cu (blue curve), pre-oxidized (red curve) and carbonized (green curve). In the FTIR curve of untreated PAN fiber, the −1 The absorption peak in the range is CH bond, located at 2243-2246cm -1 The absorption peak in the range is (C≡N) nitrile group, located at 1730-1737cm -1 The absorption peak is the C=O double bond, located at 1593-1628cm -1 The absorption peak is the CO bond, located at 1454 cm -1 The absorption peak is the symmetrical bending vibration of CH in the main chain of hydrocarbons. −1 A new peak appears around 1660cm −1The peaks on the left and right are related to the C=O bond, indicating that the formation of the cyclized structure and the introduction of oxygen functional groups in the cyclized structure are mainly from the keto group and carboxyl group formed during the oxidation process. As the degree of oxidation increases, the intensity of this peak increases. In addition, the peak at 1454 cm -1 -CH 2 The bending strength of the -CH- bond decreases, while the bending strength of the -CH- bond increases, reflecting the progress of dihydrogen reactions, i.e., stabilization reactions (i.e., cyclization, oxidation, and dehydrogenation). -1 The intensity of the absorption peak decreases, indicating that the content of nitrile groups gradually decreases as the pre-oxidation proceeds. During the carbonization process, PAN fibers are further pyrolyzed at high temperatures to remove non-carbon elements (such as H, O, N, etc.), and finally form carbon fibers. -1 The nitrile peak disappears during the carbonization process and is located at 1640 cm -1 The C=O peak will also weaken. Located at 1700-1750cm -1 The carboxyl peak is removed at high temperature, and this peak will also disappear. Located at 1050-1200cm -1 The absorption peak of CO bond appears, which is the stretching vibration peak in carbon fiber, indicating that some oxygen-containing functional groups (such as ether bond or phenolic hydroxyl group) are still retained in the carbon fiber. The infrared results prove that the preparation of carbon fiber is successful.
[0042] Figure 1 (c) is the Raman characterization of CFs-Cu, 1350 cm −1 The peak is related to the disorder or defect of the lattice (D peak), while the peak is about 1580cm −1 The peak is related to the plane vibration of the graphite lattice (G peak). During the pre-oxidation process, the intensity of the G peak may increase with the cross-linking and cyclization of the molecular chain, indicating the gradual formation of a graphitized structure in the material. With the cross-linking and cyclization of the molecular chain, the intensity of the D peak may first increase and then decrease. In the initial stage, the cross-linking and cyclization reactions may lead to an increase in the disorder of the structure, and the intensity of the D peak increases; as the reaction proceeds further, the defects may be repaired and the intensity of the D peak decreases. During the carbonization process, the PAN fiber is further pyrolyzed at high temperature to remove non-carbon elements (such as H, O, N, etc.), and gradually form carbon fibers. After high-temperature carbonization, the G peak becomes sharper, indicating a higher degree of graphitization and a more ordered lattice structure. After high-temperature carbonization, the D peak may still exist, but with lower intensity, indicating that there are still a small number of defects or edge structures in the carbon fibers. ID / IG=1.6. It also proves the successful preparation of CFs-Cu.
[0043] like Figure 2(a) shows the microscopic morphology of Cu / CFs-Cu after tableting. It can be seen that some black spots are evenly distributed in the copper matrix. The black spots are CFs-Cu. The black spots are large in mass and unevenly distributed. It may be because the CFs-Cu content is too high, resulting in aggregation during the sintering process. Figure 1 (c) is the corresponding EDS image, which proves that the black spots in the copper matrix are CF.
[0044] Figure 2 (b) is a comparison of the electrical conductivity and Vickers hardness of Cu / CFs-Cu and Cu. It can be seen from the figure that the Vickers hardness of pure copper is 70HV, and the hardness of Cu / CFs-Cu is 73.7HV, which is 5.2% higher. This may be because CFs is wrapped around the Cu particles, and Cu can effectively hinder the agglomeration of CF. In addition, the Cu particles wrapped with CFs can promote the sintering between the copper matrix and CFs, which is beneficial to improve the interface bonding strength, thereby enhancing the hardness of the copper-based composite material. The electrical conductivity of Cu is 60% IACS, and the electrical conductivity of Cu / CFs-Cu is 77% IACS, which is 28.3% higher. The change in performance may be that CFs-Cu prepared by spinning can effectively form an enhanced interface. CFs and Cu together form a multi-level conductive path, and the synergistic effect produced makes the transmission of electrons in the material more efficient. At the same time, CFs itself has a high conductivity. It can form a bridge between copper particles, allowing electrons to pass through the material more effectively, reducing the contact resistance, thereby improving the overall electrical conductivity.
[0045] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0046] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0047] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a CFs-Cu composite material, characterized in that: The steps include: S1. Preparation of PAN-Cu composite fiber: dissolving polyacrylonitrile in N,N-dimethylformamide to obtain a PAN solution, adding spherical copper powder to the PAN solution, mixing evenly to obtain a PAN-Cu dispersion, and subjecting the PAN-Cu dispersion to gas-electro-spinning to obtain a PAN-Cu composite fiber; S2. Pre-oxidation of PAN-Cu composite fiber: After drying the PAN-Cu composite fiber, place it in a carbonization furnace and keep it at 120℃~150℃ for 30min, then heat it to 180℃~200℃ and keep it for 30min, and finally heat it to 220℃~240℃ and keep it for 1h; S3. Carbonization of PAN-Cu composite fibers: The pre-oxidized composite fibers were placed in a tubular furnace, heated to 800°C-950°C in an inert gas atmosphere, and kept warm for 2 hours to obtain a CFs-Cu composite material.
2. The method for preparing the CFs-Cu composite material according to claim 1, characterized in that: The mass ratio of the polyacrylonitrile, N,N-dimethylformamide and spherical copper powder is 1:9:1-2.
3. The method for preparing the CFs-Cu composite material according to claim 1, characterized in that: The gas-electric blending method includes: injecting the PAN-Cu dispersion into a syringe, spinning with a coaxial needle, the inner shaft conveying the PAN-Cu dispersion at a stable flow rate of 4-8 mL / h, the outer shaft ejecting a high-pressure airflow of 0.35-0.55 MPa and 25-40 LPM, applying a voltage of 3-5 kV between the tip of the coaxial needle and a receiver, so that the PAN-Cu composite fiber is deposited on the receiver.
4. The method for preparing the CFs-Cu composite material according to claim 3, characterized in that: In the coaxial needle, the inner shaft is a 17-gauge needle with an inner diameter of 1.07 mm and an outer diameter of 1.70 mm; the outer shaft is a 13-gauge needle with an inner diameter of 1.90 mm and an outer diameter of 2.40 mm.
5. The method for preparing the CFs-Cu composite material according to claim 3, characterized in that: The coaxial needle moves back and forth at a speed of 10 to 30 mm / min; the distance between the coaxial needle and the receiver is 25 to 40 cm; the receiver is a roller collector with a rotation speed of 10 to 30 rpm.
6. A CFs-Cu composite material prepared by the preparation method according to any one of claims 1 to 5.
7. A Cu / CFs-Cu composite powder, characterized in that: The raw materials for preparing the Cu / CFs-Cu composite powder include the CFs-Cu composite material according to claim 6, copper powder, and ethylene glycol; the mass volume ratio of the copper powder to the ethylene glycol is 1 to 2:10; the mass ratio of the copper powder to the CFs-Cu composite material is 500 to 1000:
1.
8. The Cu / CFs-Cu composite powder according to claim 7, characterized in that: The preparation method of the Cu / CFs-Cu composite powder comprises the following steps: adding copper powder to ethylene glycol and stirring until the copper powder is evenly dispersed in the ethylene glycol; then adding the above-mentioned CFs-Cu composite material and stirring, then filtering the Cu / CFs-Cu slurry onto a polytetrafluoroethylene filter membrane through a vacuum filter, and finally placing the Cu / CFs-Cu slurry on the polytetrafluoroethylene filter membrane in a vacuum drying oven for drying to obtain the Cu / CFs-Cu composite powder.
9. A Cu / CFs-Cu bulk material, characterized in that: The raw material for preparing the Cu / CFs-Cu bulk material includes the Cu / CFs-Cu composite powder according to any one of claims 7-8.
10. The Cu / CFs-Cu bulk material according to claim 9, characterized in that: The preparation method of the Cu / CFs-Cu bulk material comprises the following steps: placing the Cu / CFs-Cu composite powder according to any one of claims 7 to 8 in a tubular furnace, heating it to 800°C to 950°C in an inert gas atmosphere, keeping it warm for 2 hours, and obtaining a reduced powder; using a powder metallurgy method to prepare a Cu-based composite material from the obtained powder; placing the Cu-based composite material in a tubular furnace, heating it to 800°C to 950°C in an inert gas atmosphere, keeping it warm for 2 hours, and sintering it.
Citation Information
Patent Citations
Method for preparing nano carbon fibre by using polyacryl-nitrile (PAN)
CN101112980A
Cu-CuO / carbon nano fiber composite and preparation method thereof
CN109399691A
Copper-based powder metallurgy friction material and preparation method thereof
CN112011748A
High-performance lithium ion battery polyacrylonitrile carbon fiber negative electrode material and preparation method thereof
CN113224292A
Coaxial phase change fiber and preparation method thereof
CN117947544A